Additional file 7 of Revisiting chloroplast genomic landscape and annotation towards comparative chloroplast genomes of Rhamnaceae - Kwanjeera Wanichthanarak; Intawat Nookaew; Phongthana Pasookhush; Thidathip Wongsurawat; Piroon Jenjaroenpun; Namkhang Leeratsuwan; Songsak Wattanachaisaereekul; Wonnop Visessanguan; Yongyut Sirivatanauksorn; Narong Nuntasaen; Chutima Kuhakarn; Vichai Reutrakul; et al. (Figshare, 2023)
Additional file 7: Table S9. The Ka/Ks ratio comparisons with V. harmandiana
Keywords: Genomics and Phylogenetic Studies